The Effectiveness of Ketapang Leaf (Terminalia catappa L.) Infusion as a Denture Cleanser for Heat-Cured Acrylic Resin Dentures in Inhibiting Candida albicans Growth - Soendoro, Ivan; Purbasari, I Gusti Ayu Kade Ira; Maker, Gede Indra Sucipta (E-Jurnal Medika Udayana; Vol 14 No 7 (2025): E-Jurnal Medika Udayana, 2025)
Tooth loss can be addressed with removable dentures. However, heat-cured acrylic resin, commonly used as a denture base material, has a drawback of porosity that facilitates the growth of Candida albicans . One method of maintenance is soaking dentures in a cleansing solution to prevent fungal growth. This study aimed to evaluate the effectiveness of Ketapang leaf ( Terminalia catappa L. ) decoction as a denture cleanser in inhibiting the growth of Candida albicans . The research design was a true experimental laboratory post-test only control group, using 30 heat-cured acrylic resin plates contaminated with Candida albicans . There were five treatment groups: a positive control group (0.5% sodium hypochlorite), a negative control group (sterile distilled water), and three groups treated with Ketapang leaf decoction at concentrations of 30%, 60%, and 90%. Samples were soaked in each treatment solution for 15 minutes and then cultured to measure fungal counts. Data analysis revealed significant differences between the decoction groups and the negative control group (p <0.05). The group with the lowest fungal count was the 30% concentration, while the highest was the 90% concentration. Ketapang leaf ( Terminalia catappa L. ) decoction effectively inhibits the growth of Candida albicans on heat-cured acrylic resin, with the optimal concentration being 30%.